PENDIDIKAN ANAK-ANAK PERSPEKTIF AL-QUR’AN DAN HADITS - Mahbub Junaidi (MIDA : Jurnal Pendidikan Dasar Islam, 2023)
Abstract Education is the basic capital to build a developed country. The development of science and technology must also be supported by the development of adequate human resources in every era. The development of human resources can only be formed in a long educational process that starts at an early age. Education in childhood is fundamental to creating ideal and superior human resources. This is because education during childhood, especially during the golden age, greatly influences the development of their intellectual potential in the future. If education at this golden age fails, it will be increasingly difficult to build superior human resources in the future. In addition to modern educational theory, religion also teaches that learning must begin from the cradle of the mother until the end of age. This means that the process of building superior and ideal human resources takes a long process. This long process is in all aspects of education, both regarding processes and materials that are appropriate to the development of the children's age. related to that, this paper intends to: First describe the meaning of education according to the terms of the al-Qur'an and hadith; The second describes the urgency of children's education; and Third describes the children's educational materials. Keywords: Children's Education, al-Qur'an and Hadith Abstrak Pendidikan merupakan modal dasar untuk membangun sebuah negara yang maju. Perkembangan ilmu pengetahuan dan teknologi harus pula ditopang oleh perkembangan sumber daya manusia yang memadai pada setiap zamannya. Perkembangan sumber daya manusia ini hanya bisa dibentuk dalam proses pendidikan yang panjang yang dimulai sejak usia dini. Pendidikan di masa anak-anak merupakan hal mendasar untuk mencetak sumber daya manusia yang ideal dan unggul. Hal ini disebakan pendidikan di masa anak-anak terlebih di masa golden age sangat mempengaruhi perkembangan potensi inetelektual mereka ke dapan. Jika pendidikan di usia emas ini gagal maka akan semakin sulit ke dapan dalam membangun sumber daya manusia yang unggul. Di samping teori pendidikan modern, agama juga mengajarkan bahwa belajar harus dimulai sejak dalam ayunan ibu hingga akhir usia. Artinya proses membangun sumber daya manusia yang unggul dan ideal butuh proses panjang. Proses panjang tersebut dalam seluruh aspek pendidikan, baik mengenai proses maupun materi yang sesuai dengan perkembangan usia anak-anak. berkaitan dengan itu, tulisan ini bermaksud: Pertama mendeskripsikan pengertian pendidikan menurut term al-quran dan hadits; Kedua mendeskripsikan urgensi pendidikan anak-anak; dan Ketiga mendeskripsikan materi pendidikan anak-anak. Kata Kunci: Pendidikan Anak, al-Qur’an dan Hadits